Modelling of condensation pressure drop for R134a and R134a-lubricant-mixtures in multiport flat tubes. (May 2020) - Knipper, Paul; Arnsberg, Jonas; Bertsche, Dirk; Gneiting, Ronald; Wetzel, Thomas
Abstract: This paper presents the results of an experimental investigation on pressure drop characteristics for R134a and R134a-lubricant mixtures in multiport flat tubes (MPFT). An experimental facility has been set up, carefully validated and used to determine the pressure drop value in the two-phase flow regime inside extruded MPFT with hydraulic diameters from 0.91 mm to 0.53 mm with either triangular or rectangular channel cross sections with and without an axial fin structure. Based on the investigation published in Knipper et al. (2019), the operating parameters have been varied within a broad range to ensure a high degree of reliability and comparability to pressure drop correlations. In addition, the nominal oil content has been varied between 0 and 7% by weight. A good agreement of the pressure drop data with several correlations can again be confirmed for most of the flat tubes. With respect to the urgent need for reliable correlations regarding low liquid only Reynolds numbers ( R e l o = 800 − 5000 ), the authors present an approach based on the Cavallini et al. (2006) correlation that is also considering the surface roughness of the tube. For both, pure R134a and R134a-PAG-oil-mixtures, a good agreement with the newly determined data can be achieved and, thus, an enlarged range of applicability can be stated.